Proyecto de normalización para el diseño de líneas de transmisión aéreas a 500 kV en el Ecuador. - Arias Pazmiño, José Leonardo (2022)
In Ecuador, the overhead transmission line designs in which the tension level is equal or above 138kV have neither regulations nor rules; hence, it is common to use INECEL regulations. This document establishes a methodology for overhead transmission lines design for tension levels of 500 kV, where general aspects are applied. These aspects involve and guarantee personnel the safety, maintenance, operation, and environmental conditions. The first chapter establishes the theoretical fundaments and methodology used, the second chapter considers the technical aspects to justify the proposal, and the third chapter details the draft standard for the design of 500 kV overhead transmission lines.